Prevalence and socio-demographic correlates of depression and anxiety among late adolescents (15 to 21 years) in Mymensingh division, Bangladesh: A cross-sectional study - Roni Khatun; Salma Akter Urme; Md. Syful Islam (PLoS ONE, 2025)
Background Depression and anxiety are prevalent mental health disorders among adolescents worldwide, including Bangladesh. However, mental health disorders are often overlooked in developing countries like Bangladesh. This study aims to assess the prevalence of depression and anxiety, as well as the socio-demographic factors that contribute to these conditions, among late adolescents aged 15–21 in Mymensingh division, Bangladesh. Methods This cross-sectional study was conducted among 400 adolescents aged 15–21 in the Mymensingh division of Bangladesh. The study used a structured questionnaire to collect sociodemographic and lifestyle-related information from the respondents. The questionnaire included PHQ-9 and GAD-7 scales to assess depression and anxiety among the respondents. Descriptive statistics, chi-square tests, and ordinal logistic regression were performed as statistical analyses of this study. Results The overall prevalence of depression was 47.8% (33.5% moderate, 10.5% moderately severe, and 3.8% severe depression), and anxiety 32.8% (31% moderate and 1.8% severe anxiety). Across most of the socio-demographic and lifestyle-related factors, the prevalence of depression and anxiety was higher among adolescent boys. Individuals aged 19–21 are most likely to experience depression and anxiety. The study found that unmarried adolescents, mobile phone users, rural adolescents, and those whose parents had no formal education were more likely to experience moderate to severe depression and anxiety than their counterparts. The ordinal logistic regression revealed that adolescents whose fathers had no formal education were 2.77 times more likely to experience depression (95% CI = 1.21–6.35, p < 0.05). Besides depression was more likely to be associated with those who were businessmen (OR = 1.95; 95% CI = 1.02–3.72, p < 0.05), and day laborers (OR = 0.41; 95% CI = 0.20–0.82, p < 0.05) and living with anxiety (OR = 0.05; 95% CI = 0.01–0.24, p <.000). Anxiety is prevalent among adolescents who had no formal education (OR = 0.15; 95% CI = 0.03–0.75, p < 0.05), no family savings (OR = 0.42; 95% CI = 0.23–0.78, p < 0.05) and depression (OR = 0.06; 95% CI = 0.01–0.22, p < 0.05). Conclusions The findings of this study emphasize the importance of screening individuals for depressive and anxiety disorder symptoms to reduce the prevalence of mental health disorders among adolescents. In addition to screening, policymakers should incorporate policies to increase access to mental health services and promote mental health education for parents and the community.